Health policy and systems research publications in Latin America warrant the launching of a new specialised regional journal - Miguel Angel González Block; Juan Arroyo Laguna; Oscar Cetrángolo; Pedro Crocco Ábalos; Ramiro Guerrero; Daniela Riva Knauth; Abdul Ghaffar; Patricia Pavón León; María del Rocío Saénz; Rosanna González McQuire; Beatriz Martínez Zavala; Emilio Gutiérrez Calderón (BMC, 2020)
Abstract Background Scientific journals play a critical role in research validation and dissemination and are increasingly vocal about the identification of research priorities and the targeting of research results to key audiences. No new journals specialising in health policy and systems research (HPSR) and focusing in the developing world or in a specific developing world region have been established since the early 1980s. This paper compares the growth of publications on HPSR across Latin America and the world and explores the potential, feasibility and challenges of innovative publication strategies. Methods A bibliometric analysis was undertaken using HPSR MeSH terms with journals indexed in Medline. A survey was undertaken among 2500 authors publishing on HPSR in Latin America (LA) through an online survey, with a 13.1% response rate. Aggregate indicators were constructed and validated, and two-way ANOVA tests were performed on key variables. Results HPSR publications on LA observed an average annual growth of 27.5% from the years 2000 to 2018, as against 11.4% worldwide and yet a lag on papers published per capita. A total of 48 journals with an Impact Factor publish HPSR on LA, of which 5 non-specialised journals are published in the region and are ranked in the bottom quintile of Impact Factor. While the majority of HPSR papers worldwide is published in specialised HPSR journals, in LA this is the minority. Very few researchers from LA sit in the Editorial Board of international journals. Researchers highly support strengthening quality HPSR publications through publishing in open access, on-line journals with a focus on the LA region and with peer reviewers specialized on the region. Researchers would support a new open access journal specializing in the LA region and in HPSR, publishing in English. Open access up-front costs and disincentives while waiting for an Impact Factor can be overcome. Conclusion Researchers publishing on HPSR in LA widely support the launching of a new specialised journal for the region with a vigorous editorial policy focusing on regional and country priorities. Strategies should be in place to support English-language publishing and to develop a community of practice around the publication process. In the first years, special issues should be promoted through a priority-setting process to attract prominent authors, develop the audience and attain an Impact Factor.